‘He or she maybe doesn't know there is such a thing as a review’: A qualitative investigation exploring barriers and facilitators to accessing medication reviews from the perspective of people from ethnic minority communities - Anna Robinson; Laura Sile; Thorrun Govind; Harpreet Kaur Guraya; Nicola O'Brien; Vicki Harris; Guy Pilkington; Adam Todd; Andy Husband (Health Expectations, 2022)
Abstract Introduction Regular reviews of medications, including prescription reviews and adherence reviews, are vital to support pharmacological effectiveness and optimize health outcomes for patients. Despite being more likely to report a long‐term illness that requires medication when compared to their white counterparts, individuals from ethnic minority communities are less likely to engage with regular medication reviews, with inequalities negatively affecting their access. It is important to understand what barriers may exist that impact the access of those from ethnic minority communities and to identify measures that may act to facilitate improved service accessibility for these groups. Methods Semi‐structured interviews were conducted between June and August 2021 using the following formats as permitted by governmental COVID‐19 restrictions: in person, over the telephone or via video call. Perspectives on service accessibility and any associated barriers and facilitators were discussed. Interviews were audio‐recorded and transcribed verbatim. Reflexive thematic analysis enabled the development of themes. QSR NVivo (Version 12) facilitated data management. Ethical approval was obtained from the Health Research Authority (ref: 21/HRA/1426). Results In total 20 participants from ethnic minority communities were interviewed; these participants included 16 UK citizens, 2 refugees and 2 asylum seekers, and represented a total of 5 different ethnic groups. Three themes were developed from the data regarding the perceived barriers and facilitators affecting access to medication reviews and identified approaches to improve the accessibility of such services for ethnic minority patients. These centred on (1) building knowledge and understanding about medication reviews; (2) delivering medication review services; and (3) appreciating the lived experience of patients. Conclusion The results of this study have important implications for addressing inequalities that affect ethnic minority communities. Involving patients and practitioners to work collaboratively in coproduction approaches could enable better design, implementation and delivery of accessible medication review services that are culturally competent. Patient or Public Contribution The National Institute for Health Research Applied Research Collaboration and Patient and Public Involvement and Engagement group at Newcastle University supported the study design and conceptualization. Seven patient champions inputted to ensure that the research was conducted, and the findings were reported, with cultural sensitivity.